Biochemical and Histopathological Effect of Combination Extract Ethanolic Turmeric (Curcuma longa) and Kalmegh (Andrographis paniculata) in Iron Overload Rat Model - Prastiyo, M. Dodik; Rujito, Lantip; Hernawati, Hernawati (Faculty of Medicine, Universitas Diponegoro, 2026)
Background: Thalassemia-β patients have erythrocyte damage that requires blood transfusion treatment. Blood transfusion treatment that is undergone has an impact on the condition of iron overload in the body. The condition of iron overload will result in oxidative stress and organ damage that requires additional therapyObjective: aimed to compare the effectiveness of turmeric and kalmegh extract doses against biochemical parameters and histopathological features of iron-induced liver Rattus Norvegicus.Methods: This study used a True-experiment research design with a post-test-only control group. A total of 30 rats were used and divided into six treatment groups, normal, deferiprone drugs, turmeric, and kalmegh extracts 100mg/KgBW, 200mg/KgBW, and 400mg/KgBW. Malondialdehyde, catalase, superoxide dismutase, and ferritin are used as biochemical parameters and hepatic histopathology is documented.Results: The results showed that there were significant improvements and differences in iron-induced rats.Conclusion: The study also showed that turmeric and kalmegh extracts had similar effects to deferiprone.